"Era uma vez um grande" : o mito da decadente aristocracia americana - Marcus Vinícius Costa Lage (2020)
This thesis aims to investigate the factors which contributed to the failure of América Futebol Clube, from Belo Horizonte, in the restricted group of major Brazilian football clubs. Therefore, it is based on the premise that the greatness of a football club in Brazil is earned not only by the results obtained in competitions and/or by the number of its fans, but also by the symbolic system representations articulated around it, capable of producing feelings of affection and disgust so laborious to sports competitions. Thereby, the central hypothesis of this research is that the elitist identity attributed to América Futebol Clube, valued and legitimized by its fans from an ambivalent memorable narrative, called here as “myth of the América Futebol Clube decadent aristocracy”, has been one of the responsible for putting the club on the sideline of the set of symbolic representation from Belo Horizonte, dominated by the supposedly popular clubs Clube Atlético Mineiro and Cruzeiro Esporte Clube. In order to certify the dominant collective memory status, this mythology is identified and analyzed on this thesis from different moments and historical documents, from chants and virtual publications by fans from the club to the club’s marketing campaigns, through journalistic texts and official historiographical manifestations about the América Futebol Clube. Nevertheless, opposed to the historical sources of the context to which it refers, this narrative highlights a series of silences and selections from the club’s past – a typical memory framing job. Thus, it turns out, even if this myth is set in the 1920s, 1930s and 1940s, its constitution, formalization and officialization process coincided with important moments of dispute over the political and administrative hegemony of the club in the second half from the 20th century and the beginning of the new millennium.